Navy En Route Care: A 3-Year Review of 428 Navy Air Evacuations. (1st March 2017) - Walrath, Benjamin; Mora, Alejandra; Ganem, Victoria; Harper, Stephen; Ross, Elliot; Kharod, Chetan; Demers, Gerard; Bebarta, Vikhyat S.
ABSTRACT: Background: Navy medical personnel have been recording en route care (ERC) missions through Search and Rescue (SAR) reports since the 1970's. Our objective was to report clinical ERC cases treated by Navy operational assets from January 2012 to January 2015. Methods: The Search and Rescue Model Manager office collects SAR reports for all patient transports involving Navy personnel and equipment. From these reports, descriptive statistics to include total number of patients transported, percentages of Advanced Life Support versus Basic Life Support transports, time of transport, and type of ERC provider for the transport were collected. Data reported as median (interquartile range) or percentages. Results: During a 3-year period, 428 patients were transported. Transport time was 54 (30–78) minutes. Missions were staffed by more than one provider 22% of the time. Individual providers included 76% Search and Rescue Medical Technicians, 25% Flight Surgeons, and 21% Other. Patients required ALS transport 54% of the time. Less than half (48%) of the patients were trauma related. Conclusion: In our review of 428 SAR reports from Navy ERC (2012–2015), we found that 76% of the missions were performed by Search and Rescue Medical Technicians and 54% met Advanced Life Support transport criteria.